EU enlargement and the portuguese economy - Barry, Frank (2022)
Enlargement will have important implications for Portugal. To some extent these are already noticeable in the wake of the Europe Agreements. Portuguese exports bear a strong similarity to those from Central and Eastern Europe and have been losing EU market share as the CEE economies expand. To this extent Portugal can be said to be ‘being squeezed from below’ in that its traditional export sectors face greater competition. At the same time, its specialisation seems to be increasingly confined to low-technology, low-added-value sectors with declining demand, as strong FDI inflows to the CEEC lead to an increasing preponderance of more dynamic sectors in their export structures. Thus, it is also being squeezed from above. This suggests that there may be substantial industrial disruption, in response to which labour market flexibility and dynamic entrepreneurial response is crucial. A worrying aspect of this is that intersectoral mobility is generally easier the more highly educated the workforce – an indicator on which Portugal scores quite poorly. Nevertheless, it is worthwhile mentioning that the Portuguese labour market displays a high degree of flexibility, consistent with its low unemployment rate of recent decades (Bover and Portugal, 2000). This will help to minimise the adjustment costs associated with increased competition from the accession states. he present paper is a broad reflection on the economic impact of Eastern enlargement on the Portuguese economy. Section 2 deals with external trade; Section 3 with inward FDI; Section 4 with migration flows and Section 5 with the Structural and Cohesion Fund programmes. Section 6 concludes.